2019
DOI: 10.21767/1791-809x.1000621
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between War Trauma, PTSD, Anxiety and Depression among Adolescents in the Gaza Strip

Abstract: Aim:The study aimed to investigate the relationship between war trauma and PTSD (Post-Traumatic Stress Disorder), anxiety and depression problems among secondary school students in Gaza Strip. Method:The study sample consisted of 408 randomly selected secondary school students (204 boys and 204 girls). Adolescents were interviewed using sociodemographic questionnaire, Gaza Traumatic Events Checklist, Birleson Self-Rating Depression Scale, and Revised Children's Manifest Anxiety Scale. Results:The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The Gaza Traumatic Events Checklist (GTEC) was the most commonly used tool to assess the EPV (n = 14) [ 28 – 30 , 33 , 37 , 39 , 41 – 45 , 47 , 50 , 51 ]. Modifications were made to the number and type of items examined in the different studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Gaza Traumatic Events Checklist (GTEC) was the most commonly used tool to assess the EPV (n = 14) [ 28 – 30 , 33 , 37 , 39 , 41 – 45 , 47 , 50 , 51 ]. Modifications were made to the number and type of items examined in the different studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported no significant relationship between proximity to the traumatic event and PTSD [ 34 ]. Fourteen studies reported that the most prevalent types of traumatic events were an indirect exposure, such as hearing drones and shelling artillery, and exposure to distressful events through the media [ 28 , 29 , 31 , 33 , 37 , 39 , 41 – 45 , 47 , 51 , 52 ]. Similar results were found among children and adolescents witnessing their fathers being detained by Israeli soldiers (n = 2) [ 40 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations